Prominent alumni: Siti Fatimah Adnan / Enabella Tasha Dennis ... [et al.] - Dennis, Enabella Tasha; Juman, Juliet Cheria; Abdul Khalik, Khairunisa; Nyareng, Rasiba (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
Siti Fatimah Adnan is the founder of Mokti's Ice Cream. She came from Perlis, a Northern state in Peninsula Malaysia. She has a degree in Technology & Plantation Management from UiTM. Siti lived in Bintulu, Sarawak as a housewife for 2 years before she started her business. She was attended an ice cream making course to learn the basics and then experimented with making her own version of the famous Sarawak dessert.